2021
DOI: 10.1016/j.ppnp.2021.103887
|View full text |Cite
|
Sign up to set email alerts
|

Gamma spectroscopy with AGATA in its first phases: New insights in nuclear excitations along the nuclear chart

Abstract: The Advanced GAmma Tracking Array (AGATA), the new generation high-resolution γray spectrometer, has seen the realization of the first phases of its construction and exploitation. A number of nuclear structure studies based on experiments utilizing the principle of γ -ray tracking were carried out in this decade. The combination of highest detection efficiency and position sensitivity allowed very selective spectroscopic studies with stable beams and the use of instable ion beams with the lowest intensities. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 350 publications
(541 reference statements)
0
3
0
Order By: Relevance
“…To date AGATA has produced 86 scientific publications (e.g. see [11]) and over 110 technical publications. This clearly demonstrates AGATA's impact but another very important outcome are the training aspects of the project, in particular for young scientists, engineers and technicians.…”
Section: Deployment and Exploitationmentioning
confidence: 99%
“…To date AGATA has produced 86 scientific publications (e.g. see [11]) and over 110 technical publications. This clearly demonstrates AGATA's impact but another very important outcome are the training aspects of the project, in particular for young scientists, engineers and technicians.…”
Section: Deployment and Exploitationmentioning
confidence: 99%
“…A degrader of 5.7 mg/cm 2 natural magnesium was positioned at different distances from the target to simulate a RDDS experiment. Examples of such experiments performed with AGATA and magnetic spectrometers can be found in the review of Bracco et al [22]. In this simulation a rectangular parallelepiped is used to simulate the geometrical opening of a magnetic spectrometer.…”
Section: Example 3 -Multi-nucleon Transfer To 62 Fementioning
confidence: 99%
“…1d and e, it is essential to accurately determine the beam properties to remove other contributions to Δβ and Δα. Bracco et al [21] suggested that to make the most of the position-sensitivity of AGATA for Doppler correction, the beam trajectory should be determined to a precision of 0.3 • , the target position to a precision of 3 mm, and the β for the beam determined, eventby-event, to a precision of better than 0.3%. To achieve this in the PreSPEC campaign, the trajectory and velocity of the fragments were determined to high precision by the LYCCA detectors [16].…”
Section: In-beam Spectroscopy With High-velocity Beamsmentioning
confidence: 99%